Feline fetal mummification - ANTOINE, D; MURUGAVEL, K; ALPHONSE, R M D; RAJU, M S (The Indian Journal of Animal Reproduction, 2002)
A case of fetal mummification in a cat and its successful therapeutic management through surgical approach hasbeen reported in the present paper.
Keywords: Fetal mummification; feline